Sanksi Pidana Terhadap Pelanggaran Hak Cipta Situs Layanan Streaming Sepak Bola dalam Perspektif Hukum Pidana Islam - Munif Hanafi, Al; Mukhsin, Abdul (UNES Law Review, 2023)
The background to this investigation is the rise in piracy and piracy of soccer streaming services, which are often exploited for individual and collective benefit. Such infringements result in significant losses for the copyright licensors of soccer streaming services. This type of research includes documents, books, legal research results, law journals, and library searches using the Internet. This type of research is qualitative research that uses a descriptive analytical format and a prescriptive legal approach. Specifically, legal research is analyzed based on legal norms and legal norms. In terms of Islamic criminal law, the criminal penalty for copyright infringement on a football streaming service is amputation if the stolen goods reach the Nishab. On the other hand, according to positive law, the penalty is a maximum of four years imprisonment and/or a fine of up to one billion rubles (one billion rupiah). In this investigation, the crime of copyright infringement of soccer streaming services is considered Jarimah Sariqah. Jalima Sarika is the act of an amkaraf (an adult, alert, and healthy person) removing another person's property from a storage location without their permission or consent for the purpose of possessing or controlling it (in secret) for a period of time. is. Owner Nisab.